2018
DOI: 10.1186/s13034-018-0248-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional family therapy in adolescents with a cannabis use disorder: long-term effects on delinquency in a randomized controlled trial

Abstract: BackgroundSubstance use and delinquency are considered to be mutual risk factors. Previous studies have shown that multidimensional family therapy (MDFT) is effective in tackling both conditions on the short term. The current study examines the long-term effects of MDFT on criminal offending.Methods109 adolescents with cannabis use disorder and comorbid problem behavior were randomly assigned to either MDFT or cognitive behavioral therapy (CBT). Police arrest data were collected for 6 years: 3 years prior to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…This suggests MDFT is a promising alternative to residential treatment among youth who meet criteria for a higher level of care and may be less burdensome as an outpatient treatment option [15•]. In addition to demonstrating effectiveness in substance use treatment, MDFT was found to be as effective as CBT in reducing delinquency among adolescents with cannabis use disorder [16] and was more cost effective than CBT when considering costs of delinquency, and not just annual direct medical costs [17].…”
Section: A Family-based Therapymentioning
confidence: 99%
“…This suggests MDFT is a promising alternative to residential treatment among youth who meet criteria for a higher level of care and may be less burdensome as an outpatient treatment option [15•]. In addition to demonstrating effectiveness in substance use treatment, MDFT was found to be as effective as CBT in reducing delinquency among adolescents with cannabis use disorder [16] and was more cost effective than CBT when considering costs of delinquency, and not just annual direct medical costs [17].…”
Section: A Family-based Therapymentioning
confidence: 99%
“…The long-term effects of home-based treatment have been examined with regard to drug abuse and delinquency. van der Pol et al (2018) found that 3 years after treatment, delinquency and cannabis abuse had significantly declined, although no difference was found between multidimensional family therapy and cognitive behavioral therapy. In another study, dealing with juvenile sexual offenders, the effects of multisystemic therapy were more sustained than for group cognitive behavioral therapy (Letourneau et al, 2013).…”
Section: Long-term Effects Of Treatment Of Multi-problem Familiesmentioning
confidence: 99%
“…Eight in ten were boys. Seven in ten were of Dutch (Van Der Pol et al 2018). At the time of treatment entry, 66% had a police arrest history (for more information see Table 1).…”
Section: Samplementioning
confidence: 99%
“…For these youths, arrest data were retrieved for 3 years preceding and 3 years following treatment entry. The number of police arrests which rose in 3 years before treatment was initiated and dropped sharply in 3 years thereafter, with no difference seen between MDFT and CBT in the follow-up period, possibly with exception of a property crime measure (Van Der Pol et al 2018).…”
Section: Introductionmentioning
confidence: 97%